2022
DOI: 10.1021/acs.jproteome.2c00337
|View full text |Cite
|
Sign up to set email alerts
|

Coupling High-Field Asymmetric Ion Mobility Spectrometry with Capillary Electrophoresis-Electrospray Ionization-Tandem Mass Spectrometry Improves Protein Identifications in Bottom-Up Proteomic Analysis of Low Nanogram Samples

Abstract: In this work, we pioneered the assessment of coupling high-field asymmetric waveform ion mobility spectrometry (FAIMS) with ultrasensitive capillary electrophoresis hyphenated with tandem mass spectrometry (CE-MS/MS) to achieve deeper proteome coverage of low nanogram amounts of digested cell lysates. An internal stepping strategy using three or four compensation voltages per analytical run with varied cycle times was tested to determine optimal FAIMS settings and MS parameters for the CE-FAIMS-MS/MS method. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…In the hyperSCP workflow, high labeling efficiency is necessary for accurate quantification. To determine the SILAC labeling efficiency, the cell samples were prepared in bulk, 38 analyzed by nanoLC−MS, and databasesearched using PD 2.5, with the label 13 C 6 15 N 2 (+8.014 Da, K) and label 13 C 6 15 N 4 (+10.008 Da, R) selected as dynamic modifications. The results indicated that 97% of lysines and 98% of arginines were labeled in the SILAC-heavy cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the hyperSCP workflow, high labeling efficiency is necessary for accurate quantification. To determine the SILAC labeling efficiency, the cell samples were prepared in bulk, 38 analyzed by nanoLC−MS, and databasesearched using PD 2.5, with the label 13 C 6 15 N 2 (+8.014 Da, K) and label 13 C 6 15 N 4 (+10.008 Da, R) selected as dynamic modifications. The results indicated that 97% of lysines and 98% of arginines were labeled in the SILAC-heavy cells.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…HeLa, A549, K562, and HFL1 cells were obtained from ATCC (Manassas, VA) and cultured at 37 °C with 5% CO 2 using cell culture medium with 10% fetal bovine serum and 1% penicillin/streptomycin. Non-SILAC ("light") cells were cultured in regular RPMI 1640 medium, while the SILAC-labeled ("heavy") cells were cultured in the RPMI 1640 medium in which the lysine and arginine were replaced with 13 C 6 15 N 2 L-lysine-2HCl and 13 C 6 15 N 4 L-arginine-HCl. The cells were cultured as reported 38 and split upon reaching ∼70% confluency.…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of sheathless CE‐MS/MS with the high‐field asymmetric waveform ion mobility spectrometry that functions as an ion‐selective device, reduced background noise, and increased S/N of the CE‐MS analyses [118]. The optimized method with high‐field asymmetric waveform ion mobility spectrometry identified from 1 ng of standard HeLa protein digest 16%, 25%, and 22% of more proteins, peptide groups, and peptide spectrum matches, respectively, than solely CE‐MS/MS.…”
Section: Bottom‐up Proteomicsmentioning
confidence: 99%
“…Combining multiple compensation voltages (CVs) within a single run or between runs improves whole proteome coverage in cell lysates. , For example, Pfammatter et al observed a 30% gain in unique peptide identification using FAIMS compared with non-FAIMS analysis of HEK 293 cells . Other studies using HeLa protein digest such as Johnson KR et al, Greguš M et al, and Cong Y et al concurrently showed the addition of FAIMS had significantly increased protein and peptide identifications than without FAIMS. In a few recent studies working with various tissue samples, including brain autopsies, tumor biopsies, and paraffin embedded tissues (lymph node, lung, and prostate), the addition of FAIMS also showed an enhanced detection of nonredundant proteoforms, increased proteome sensitivity, or substantially reduced sample handling. As the cardiac proteome consists of large dynamic range, it remains unclear whether FAIMS can detect peptides and the less abundant proteins from the cardiac proteome that is comparable with previous established fractionation methods.…”
Section: Introductionmentioning
confidence: 99%